Towards a unified theory of brand equity: conceptualizations, taxonomy and avenues for future research - Davcik, N.; Vinhas da Silva, R.; Hair, J. F. (Journal of Product and Brand Management, 2015)
This paper aims to look into contemporary thinking within the brand equity paradigm, with a view to establishing avenues for further research on the drivers of brand equity formation, enabling a more in-depth understanding of the antecedents of brand equity and its determinants, as well as the development of an improved instrument to measure brand equity. We develop the relating conceptual study through differentiation and integration as a specific conceptual goal. We present a taxonomic framework of brand equity grounded on a synthesis of contemporary approaches to the theme. In so doing we identify gaps in the brand equity literature, which we hope will serve as beacons for future research and provide valuable theoretical insights on the determinants of brand equity formation and the development of better brand equity measurement tools. We argue that the unifying brand equity theory should be based on three pillars: stakeholder value, marketing assets and brand financial performance outputs.